Acute Oxalate Nephropathy Caused by Excessive Vegetable Juicing and Concomitant Volume Depletion - Harshad Chaudhari; Jennine Michaud; Nityasree Srialluri; Smita Mahendrakar; Christine Granz; Michael Yudd (Case Reports in Nephrology)
Acute oxalate nephropathy (AON) induced by high dietary intake of oxalate-rich food is a rare cause of acute kidney injury and end-stage renal disease (ESRD). We describe a 68-year-old man with adequate baseline renal function who developed severe AON and ESRD. Six months earlier, he started a daily oxalate-rich fruit and vegetable juice diet high in spinach, with a calculated daily oxalate dietary intake of 1500 mg, about 10 times a typical diet. Renal biopsy showed extensive tubular oxalate deposits and acute tubular damage; the renal tissue was relatively free of chronic changes such as glomerulosclerosis, tubular atrophy, and interstitial fibrosis. A year later, he remains dialysis dependent.